CTNI-27. FIRST-IN-PEDIATRICS PHASE I STUDY OF GDC-0084 (PAXALISIB), A CNS-PENETRANT PI3K/mTOR INHIBITOR, IN NEWLY DIAGNOSED DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG) OR OTHER DIFFUSE MIDLINE GLIOMA (DMG). (9th November 2020) - Tinkle, Christopher; Huang, Jie; Campagne, Olivia; Pan, Haitao; Onar-Thomas, Arzu; Chiang, Jason; Klimo, Paul; Boop, Rick; Patay, Zoltan; Shulkin, Barry; Lucas, John; Merchant, Thomas; et al.
Abstract: BACKGROUND: GDC-0084 is an oral, highly selective and potent inhibitor of class I PI3K and moderate inhibitor of mTOR, with an established adult maximum tolerated dose (MTD) of 60 mg/day and evidence of brain tumor penetration in adult recurrent glioblastoma. METHODS: We used a rolling-6 design to evaluate the safety and pharmacokinetic (PK) properties and establish the pediatric MTD of once-daily GDC-0084 administered after focal RT in children with newly diagnosed DIPG and histone H3 K27M-mutant DMG. Non-compartmental plasma PK analyses were performed using samples collected on cycle 1 days 1–3 after single-dose and day 28 at steady-state. RESULTS: Twenty-five patients have been enrolled, 16 of whom were treated at study dosage levels of 27 mg/m 2 (n=11) and 35 mg/m 2 (n=5). Two dose limiting toxicities (DLTs) observed at 35 mg/m 2 were grade 3 mucositis and grade 3 rash. Grade 3 hyperglycemia was the only DLT at 27 mg/m 2 . The most frequent grade 3 or 4 adverse events attributed to GDC-0084 were rash (5 patients), neutropenia (4), and hyperglycemia (2). After single-dose, GDC-0084 exposures (AUC0-48h ) at 27 and 35 mg/m 2 were 3399±1301 and 4462±2868 hr·ng/mL, respectively. Mean GDC-0084 half-life was 20.6±9.1 hr, comparable to that observed in adults. CONCLUSIONS: The dosage of 27 mg/m 2 has been established as the pediatric MTD of GDC-0084, which is approximately equivalent to 80% of the adult MTD. At 27 mg/m 2, GDC-0084 is well tolerated in children where the spectrum of toxicities is similar to those observed in adults and consistent with this class of agents.